2011
DOI: 10.5194/adgeo-30-17-2011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in rainfall and tropical cyclone activity over South and Southeast Asia

Abstract: Abstract. Long-term changes in rainfall and associated tropical cyclone (TC) activity in transition seasons between the wet and dry seasons in South and Southeast Asia, namely boreal spring and fall, were examined, using gridded rainfall, TC tracks, and reanalysis datasets, the focus of discussion being the long-term changes in coastal regions. It was found that long-term changes in rainfall during the transition seasons in South and Southeast Asia were closely associated with those in TC activity over the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Of specific interest to historical climate change in Vietnam and surrounding regions are studies of Manton et al (2001), Takahashi (2011), Kajikawa et al (2012). Endo et al (2009) found that heavy precipitation increases in southern Vietnam but decreases in northern Vietnam during the 1950s to early 2000s.…”
Section: Introductionmentioning
confidence: 99%
“…Of specific interest to historical climate change in Vietnam and surrounding regions are studies of Manton et al (2001), Takahashi (2011), Kajikawa et al (2012). Endo et al (2009) found that heavy precipitation increases in southern Vietnam but decreases in northern Vietnam during the 1950s to early 2000s.…”
Section: Introductionmentioning
confidence: 99%
“…Chan and Xu () highlight similar decadal and multi‐decadal trends in the number of landfalling tropical cyclones (ATCs) over Southeast. ATCs have been reported to influence rainfall in South East Asia (Takahashi, ). Hence, the intensification of ATCs activity (Takahashi, ) might relate to the observed intensification in rainfall in late Fall and Winter in Central Vietnam.…”
Section: Resultsmentioning
confidence: 97%
“…ATCs have been reported to influence rainfall in South East Asia (Takahashi, ). Hence, the intensification of ATCs activity (Takahashi, ) might relate to the observed intensification in rainfall in late Fall and Winter in Central Vietnam.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A geostatistical simulation algorithm was also used to produce 100 equiprobable maps of the SPI for each year and this gridded data set was used to produce yearly scenarios of the SPI from 1940 to 1999 and uncertainty evaluations of the scenarios produced. Takahashi (2011) investigated the longterm changes in rainfall and associated tropical cyclone activity in transition seasons (between wet and dry seasons) in South and Southeast Asia, using gridded rainfall, tropical cyCorrespondence to: S. Michaelides (silas@ucy.ac.cy) clone tracks and reanalysis datasets. The long-term changes in coastal regions were discussed along with the fact that long-term changes in rainfall during the transition seasons in South and Southeast Asia are closely associated with those in tropical cyclone activity over the north Indian Ocean and South China Sea.…”
mentioning
confidence: 99%